A BALANCED PERFORMANCE MEASUREMENT SYSTEM FOR AUTOMOTIVE SPARE PARTS SUPPLY CHAIN - Zineb ACHETOUI; Charif MABROUKI; Ahmed MOUSRIJ (Scientific Journal of Silesian University of Technology. Series Transport)
This paper aims to provide a performance measurement system for the automotive spare parts supply chain. We focus on an independent distributor belonging to an independent channel. The framework encompasses different performance aspects for a high supply chain visibility, as well as the required categories, subcategories and key performance indicators for the automotive spare parts supply chain performance measurement. The framework is the first contribution that advances the performance measurement in the automotive aftermarket and allows assessing the performance of the automotive spare parts supply chain as a whole.